Doctors' perceived working conditions and the quality of patient care: a systematic review. Issue 4 (2nd October 2019) - Teoh, Kevin; Hassard, Juliet; Cox, Tom
ABSTRACT: Numerous reports advocate improving doctors' working conditions as an important part of initiatives to enhance the quality of patient care. However, the research literature is not clear on this underlying relationship. This systematic review examines the evidence on the relationship between the working conditions perceived by doctors and the quality of patient care. Seven electronic databases were searched, with 21 studies from six countries included in the review. The findings highlight questions on how quality of care is constructed and measured, as the presence of these relationships varied by the outcome measure used. A greater number of significant relationships were observed for clinical excellence and patient safety than patient experience. The reviewed literature reflects a lack of theoretical underpinning and consideration of the mechanisms underlying pathways between doctors' perceived working conditions and quality of care. It also does not capture the complexities within the healthcare sector, nor the wider theoretical and empirical developments in the field. Therefore, a definitive relationship between doctors' perceived working conditions and the quality of patient care should be considered with caution. Future research should account for the observed methodological and theoretical limitations to better understand the nuances within this complex, but important relationship.